2022
DOI: 10.1021/acscatal.2c03162
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrocatalytic Oxidation of Glycerol via Promoted OH* Generation over Single-Atom-Bismuth-Doped Spinel Co3O4

Abstract: The renewable electricity-driven electrocatalytic oxidation of biomass represents a pathway to produce value-added chemicals from waste biomass such as glycerol (a byproduct of industrial biodiesel production). However, it remains difficult to design an efficient electrocatalyst with explicit structure–property relationships. Herein, we report a single-atom bismuth (Bi)-doping strategy to endow Co3O4 with enhanced activity and selectivity toward electrocatalytic glycerol oxidation reaction (GOR). Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 63 publications
(101 reference statements)
3
58
0
Order By: Relevance
“…Raman spectra of pure Co 3 O 4 , Co 3 O 4– x , and Ru/Co 3 O 4– x display similar patterns, hence suggesting their identical same structure information. Figure d presents three obvious evident Raman peaks located at 467, 510, and 675 cm –1 , corresponding to E g , F 2g , and A 1g modes of crystalline Co 3 O 4 , respectively. Strikingly, the peaks of Co 3 O 4– x and Ru/Co 3 O 4– x are slightly shifted and broadened (Figure e) due to the existence of oxygen vacancies and Ru doping. , From Brunauer–Emmett–Teller (BET) analysis (Figure f), Co 3 O 4 , Co 3 O 4– x , and Ru/Co 3 O 4– x samples possess specific surface areas of 54.7, 63.2, and 65.7 m 2 /g, respectively. The large surface area of Ru/Co 3 O 4– x is due to the continuous ultrasonication and stirring treatment, illustrating that this synthetic strategy could not alter the surface areas greatly.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectra of pure Co 3 O 4 , Co 3 O 4– x , and Ru/Co 3 O 4– x display similar patterns, hence suggesting their identical same structure information. Figure d presents three obvious evident Raman peaks located at 467, 510, and 675 cm –1 , corresponding to E g , F 2g , and A 1g modes of crystalline Co 3 O 4 , respectively. Strikingly, the peaks of Co 3 O 4– x and Ru/Co 3 O 4– x are slightly shifted and broadened (Figure e) due to the existence of oxygen vacancies and Ru doping. , From Brunauer–Emmett–Teller (BET) analysis (Figure f), Co 3 O 4 , Co 3 O 4– x , and Ru/Co 3 O 4– x samples possess specific surface areas of 54.7, 63.2, and 65.7 m 2 /g, respectively. The large surface area of Ru/Co 3 O 4– x is due to the continuous ultrasonication and stirring treatment, illustrating that this synthetic strategy could not alter the surface areas greatly.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, FA is detected as the main product with a high selectivity of 85% (Scheme a, red dashed box). The unique bonding mode, full conversion of C2–C3 intermediates, and retarded overoxidation of BVO/TANF result in highly selective FA generation on BVO/TANF (Scheme b) …”
Section: Discussionmentioning
confidence: 99%
“…The unique bonding mode, full conversion of C2−C3 intermediates, and retarded overoxidation of BVO/TANF result in highly selective FA generation on BVO/TANF (Scheme 3b). 66…”
Section: Charge Recombination and Hole Transfer Kineticsmentioning
confidence: 99%
“…Moreover, the authors also suggested that enhanced product selectivity was due to regioselective oxidation and weak adsorption of the products on the surface of Bi 2 WO 6 . 49…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%